EKONOMI POLITIK RESTRUKTURISASI BUMN - Sanerya Hendrawan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
For more than a decade Indonesian state enterprises have been under strong pressures to change. Their poor performance due to incompetent management and strong politization as well as budget deficit that has plagued the country since 1990s have led to the privatization move. Although a solid institutional setup for the permanent improvement of state enterprise performance is gradually established, the government remains unclear with regard to what extent it pursues the balance between state and private enterprises in the future. This should get attention considering the likely increasing numbers of state enterprises sold to foreign enterprises through the recent privatization initiative. In the political economic context of Indonesia, state enterprises have been historically assumed to play a balancing role, especially to domestic Chinese and foreign private capitals. Thus,with privatization changing the existing balance gradually more in favour of foreigncapitals, it creates impression that economic nationalism is no longer relevant in theIndonesian economy.